Solid waste-derived cao-based sorbent pellets for solar irradiation-assisted driven calcium looping: Spatially decoupled solar-harvesting and CO2 sorption - Xunqian Tian; Jiyun Mao; Zixiang Wang; Renhai Wang; Ruilin Wang; Rongyue Sun; Jian Sun (Chemical Engineering Journal, 2026)

Experimental and numerical investigation of free-surface hydrodynamic interference between tandem hydrofoils - Ruilin Wu; Pengnan Sun; Wenxin Li; Yifan Chen (Ocean Engineering, 2026)

Melatonin Delays Flowering Time in Prunus sibirica - Ruilin Liu; Yongqiang Sun; Jianhua Chen; Haiqi Wang; Shengjun Dong (Journal of Plant Growth Regulation, 2026)

Development of heterotrophic nitrifying aerobic denitrifying bacteria powder and its nitrogen removal performance - Ruilin Cai; Mengqing Qi; Ye Sun; Yiyang Yu; Wenge Yang; Yonghong Hu (Journal of Water Process Engineering, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

A new insight into PCDD/Fs degradation from MSWI fly ash during CaCO3 oligomer crystallization via low-temperature thermal induction - Yizhe Shen; Jie Chen; Dianwei Sun; Ruilin Zhu; Jie Liu; Haijun Wang; Hong Yu; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Waste Management, 2026)

A 15,000-year Temperature record from the northern boundary of the east asian summer monsoon based on lacustrine brGDGTs - Nan Zhan; Zeyang Zhu; Pingping Li; Luo Wang; Ruilin Wen; Manman Xie; Qing Sun; Guoqiang Chu (Quaternary Science Reviews, 2026)

Accelerated gelation and strengthened network formation in whey-pea binary protein systems via linear or branched β-glucans - Bowen Zou; Xiaohan Zheng; Ruilin Sun; Xiaokang Na; Ming Du; Chao Wu (Carbohydrate Polymers, 2026)

Optimizing a prediction model for engineering disturbance hazard susceptibility along the China-Nepal highway in the Qinghai-Tibet plateau - Lei Li; Zhiqing Li; Shuangjiao Wang; Kai Sun; Ruilin Hu (Bulletin of Engineering Geology and the Environment, 2026)

Establishment and application of DNA molecular fingerprint of kernel-used apricots using capillary electrophoresis with fluorescence-labeled simple sequence repeats (SSR) - Yongqiang Sun; Jianhua Chen; Yuncheng Zhang; Ruilin Liu; Shipeng Wang; Shengjun Dong (Genetic Resources and Crop Evolution, 2025)

A machine learning and counterfactual reasoning-integrated decision framework for cadmium remediation: Predictive optimization and cost-benefit analysis driven by iron plaque regulation - Ye Li; Jie Hou; Mengqi Liu; Ruilin Li; Zhaolin Du; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Hazardous Materials, 2025)

Rapid and automated mapping method of Spartina alterniflora combines tidal imagery and phenological characteristics - Ruilin Wang; Yanan Su; Xiaofang Sun; Meng Wang; Min Feng (Environmental Monitoring and Assessment, 2025)

Monitoring the nicotine delivery stability in electronic cigarettes based on in-situ AS/SRD/FOS technology - Shuai Yuan; Shihao Sun; Ruilin Qin; Peng Li (Analytica Chimica Acta, 2025)

Study on cumulative plastic deformation and resistivity-based damage evolution of frozen soil-rock mixtures under cyclic loading - Kai Sun; Zhiqing Li; Lei Li; Ruilin Hu; Weilin Pan; Wenbo Su (Soil Dynamics and Earthquake Engineering, 2025)

Propagation threshold from meteorological to agricultural drought and its potential influence factors - Peng Sun; Ruilin Liu; Rui Yao; Xihui Gu; Aminjon Gulakhmadov; Dongdong Kong; Xiang Zhang (Journal of Hydrology, 2025)

Mediating Zn loading on Cu-Zn bimetallic catalyst for electrochemical CO2 reduction into tunable syngas - Yafei Guo; Yangna Luo; Hanlin Wang; Xianglin Chen; Xiang Liu; Benshuai Guo; Jian Sun; Ruilin Wang; Weiling Li; Chuanwen Zhao (Fuel, 2025)

Temperature variability in northeastern China over the Past 2000 Years: Linkages with the Arctic oscillation and solar activity - Nan Zhan; Fangang Zeng; Qi Li; Manman Xie; Ruixia Hao; Li Pingping; Ruilin Wen; Luo Wang; Qing Sun; Guoqiang Chu (Quaternary International, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Cobalt-catalyzed reversible deposition/dissolution of MnO2 for enhancing the long-cycle stability of aqueous Zn-Mn batteries - Changpeng Xian; Ruilin He; Qianwei Chen; Qiulin Li; Yandong Ma; Shu-juan Bao; Wei Sun; Hao Chen; Maowen Xu (Chemical Engineering Journal, 2025)

Hydrophobic interface-assisted casting of core–shell CaO-based pellets for thermochemical energy storage: Assembly mechanism for dark Mn-based shell - Yi Shi; Jian Sun; Yun Long; Ruilin Wang; Zijian Zhou; Long Jiang; Chuanwen Zhao (Chemical Engineering Journal, 2025)

O-PTIR reveals the thermal evolution mechanism of ultra-deep light oil: Based on molecular structure and chemical composition analysis - Ruilin Wang; Jiakai Hou; Ting Wang; Yang Sun; Ziguang Zhu; Zhigang Wen; Yanqing Zhu; Zhiyao Zhang; Yaling Zhu; Guangyou Zhu (Chemical Engineering Journal, 2025)

Study on the extension mechanism of fissures in expansive soil based on fracture mechanics test method - Youxing Kong; Zhiqing Li; Kai Sun; Zhiyu Qi; Ruilin Hu (Engineering Geology, 2024)

Comparison of selection methods to establish a core collection of the Siberian apricot using trait and SSR data - Yongqiang Sun; Yuncheng Zhang; Jianhua Chen; Ruilin Liu; Shipeng Wang; Shengjun Dong (Tree Genetics & Genomes, 2024)

Undervalued role of metal-carbon junction in selective generation of H2O2: An example of the zinc-carbon junction edge providing asymmetric active sites for efficient oxygen reduction - Chengyu Duan; Yinglong Lu; Zheshun Ou; Mengdi Sun; Guanghui Luo; Huimin Liu; Ruilin Wang; Yijie Wang; Zhuofeng Hu (Chemical Engineering Journal, 2024)

Provincial equity and enhanced health are key drivers for China's 2060 carbon neutrality - Jiaxin Dong; Siwei Li; Yisheng Sun; Weishu Gong; Ge Song; Yu Ding; Jie Yang; Mengfan Teng; Ruilin Wang; Jia Xing; Yang Ou; Wei Gong (Journal of Cleaner Production, 2024)

A support vector machine model of landslide susceptibility mapping based on hyperparameter optimization using the Bayesian algorithm: a case study of the highways in the southern Qinghai–Tibet Plateau - Kai Sun; Zhiqing Li; Shuangjiao Wang; Ruilin Hu (Natural Hazards, 2024)

Dynamic simulation and experimental studies of molecularly imprinted label-free sensor for determination of milk quality marker - Axin Liang; Tianjian Lv; Bingchen Pan; Ziyu Zhu; Ruilin Haotian; Yao Xie; Liquan Sun; Jiangjiang Zhang; Aiqin Luo (Food Chemistry, 2024)

Errors of Tropical Cyclone-Induced Ocean Waves in Reanalysis Using Buoy Data - Yalan Zhang; Wei Zhong; Zhihao Feng; Ruilin Wang; Yuan Sun; Zongbao Bai (Journal of Marine Science and Engineering, 2024)
Due to limited in-situ ocean observations, reanalysis data are often considered as an important source for studying tropical cyclone (TC)-induced ocean waves. Here, we introduced a method to quantitatively evaluate the errors of TC-induced ocean waves in reanalysis datasets. The TC data are from the IBTrACS dataset. We compared TC-induced ocean waves in two reanalysis datasets (i.e., ERA5 and WAVERYS) with those in buoy data when TCs are near the buoy stations. We showed that the errors of TC-induced ocean waves in WAVERYS and ERA5 are similar, because the surface winds in these two datasets are the same. We noticed that the errors in the North Pacific are remarkably smaller than those in the North Atlantic due to more realistic probability density of TC-induced ocean waves in the North Pacific compared with those in the North Atlantic. Moreover, the errors are strongly related to significant wave height (SWH) and the distance from TC center. The larger the SWH and the shorter the distance, the larger the error. Furthermore, the errors in TC-induced ocean waves decreased significantly over the past decades.

Evaluating implied urban nature vitality in San Francisco: An interdisciplinary approach combining census data, street view images, and social media analysis - Mingze Chen; Yuxuan Cai; Shuying Guo; Ruilin Sun; Yang Song; Xiwei Shen (Urban Forestry & Urban Greening, 2024)

Mobile genetic elements affect the dissemination of antibiotic resistance genes (ARGs) of clinical importance in the environment - Ye Li; Ruilin Li; Jie Hou; Xuan Sun; Yajun Wang; Linyun Li; Fengxia Yang; Yanpo Yao; Yi An (Environmental Research, 2024)

Model for Wastage Allowance and Strength Properties of Pipe Piles Exposed to Marine Corrosion - Ruilin Xia; Yordan Garbatov; Changyong Liu; Mingyang Sun (Journal of Marine Science and Engineering, 2024)
The study’s objective is to analyze the mechanical properties of steel pipe piles as a part of a trestle bridge subjected to five years of natural marine corrosion degradation. Sixteen tensile specimens are extracted from the steel pipe piles in the splash, tidal, and immersion zones. The experimental tensile test results are used to establish regression equations defining the elastic modulus, yield strength, strain hardening index, and strength coefficient for the true stress–strain curves of the three regions. A non-linear time-dependent mathematical model is exploited to identify the corrosion degradation, using the data from one single corrosion degradation measurement campaign. The analysis indicates that the splash zone is experiencing the most severe corrosion degradation, and there are progressive losses in the mechanical properties of each zone as the corrosion degradation progresses. The established relationships of the mechanical properties, as a function of the ratio of corroded plate thickness to the as-built one, can be used as a fast-engineering approach to identify the mechanical properties of severely corroded piles. The corrosion degradation allowance is also defined using the first-order reliability method, accounting for existing uncertainties covered by the partial safety factors. By examining the impact of marine corrosion on the mechanical properties of marine structures and developing predictive models to assess the corrosion’s effect on material strength and corrosion allowance, the study aims to improve offshore structures’ safety, design, and maintenance.

Simultaneous separation and analysis of multiple doxorubicin hydrochloride liposomes forms in serum by circular nonuniform electric field gel electrophoresis - Peijie Xie; Xinlei Yang; Zakia Fatima; Ruilin Yang; Huaze Sun; Yuhang Xing; Xin Xu; Jingkai Gu; Lu Liu; Donghao Li (Analytica Chimica Acta, 2024)

Correlation between microbial community succession and flavor substances during fermentation of Yongchuan Douchi - Lin Lan; Jingxin Wang; Shengyu Wang; QiaoLing He; Ruilin Wei; Zaixing Sun; Shuhua Duan; Yufeng Li (Food Bioscience, 2023)

Responses of agricultural drought to meteorological drought under different climatic zones and vegetation types - Peng Sun; Ruilin Liu; Rui Yao; Hao Shen; Yaojin Bian (Journal of Hydrology, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

Histone deacetylase SirE regulates development, DNA damage response and aflatoxin production in Aspergillus flavus - Meifang Wen; Huahui Lan; Ruilin Sun; Xuan Chen; Xin Zhang; Zhuo Zhu; Can Tan; Jun Yuan; Shihua Wang (Environmental Microbiology, 2022)
Aspergillus flavus is a ubiquitous saprotrophic soil‐borne pathogenic fungus that causes crops contamination with the carcinogen aflatoxins. Although sirtuin E ( SirE ) is known to be a NAD ‐dependent histone deacetylase involved in global transcriptional regulation. Its biological functions in A. flavus are not fully understood. To explore the effects of SirE , we found that SirE was located in the nucleus and increased the level of H3K56 acetylation. The Δ sirE mutant had the most severe growth defect in the sirtuin family. The RNA‐Seq revealed that sirE was crucial for secondary metabolism production as well as genetic information process and oxidation–reduction in A. flavus . Further analysis revealed that the Δ sirE mutant increased aflatoxin production. Both the sirE deletion and H3K56 mutants were highly sensitive to DNA damage and oxidative stresses, indicating that SirE was required for DNA damage and redox reaction by the H3K56 locus. Furthermore, the Δ sirE mutant displayed high sensitivity to osmotic stress and cell wall stress, but they may not be associated with the H3K56 . Finally, the catalytic activity site N192 of SirE was required for regulating growth, deacetylase function and aflatoxin production. Together, SirE is essential for histone deacetylation and biological function in A. flavus.

Research on target detection of Engraulis japonicus purse seine based on improved model of YOLOv5 - Jiaze Zhang; Shuxian Wang; Shengmao Zhang; Fenghua Tang; Wei Fan; Shenglong Yang; Yongwen Sun; Yang Liu; Wenbin Zhu; Shan Zhang; Ruilin He (Frontiers in Marine Science, 2022)
The refined monitoring and identification of fishing operations by fishing vessels is of great significance and value to fishing vessels. In order to solve the problem of inaccurate statistics of current Engraulis japonicus fishing quota and classification, this paper proposes an improved identification algorithm based on YOLOv5. This method introduces the SENet attention mechanism into the YOLOv5 backbone network structure, integrates the target information in different periods of fishing operations, reduces the interference of complex backgrounds, improves the precision of model detection, and ensures real-time detection efficiency. The artificially shot Engraulis japonicus videos are used as the dataset of the study, and the video is converted into a picture format to realize pre-labeling and processing. The 5550 images are divided into the training set, validation set, and test set according to 8:1:1. In order to verify the validity of the data, a set of in the control experiment, the YOLOv5 backbone network was replaced by MobileNetV2 and the SENet attention mechanism was introduced, and four models were implemented for comparison. The experimental results show that the research algorithm can obtain a mean average precision (mAP) of 99.3%, a precision of 98.9%, and a recall of 98.7%, which are improved by 1.4%, 1.7% and 2.5% respectively compared with the original model. The experimental results match the expectations. According to the statistics of some categories, the Kalman filter and the Hungarian matching method are used to count the main categories of fishing baskets, and an accuracy of 96.5% can be obtained. The threshold method for fishing nets and processing vessels can obtain 85.8% and 75% accuracy. These results shows that this target detection research can provide new ideas for job identification of Engraulis japonicus and provide auxiliary means for job statistics.

Histone acetyltransferases MystA and MystB contribute to morphogenesis and aflatoxin biosynthesis by regulating acetylation in fungus Aspergillus flavus - Xuan Chen; Lianghuan Wu; Huahui Lan; Ruilin Sun; Meifang Wen; Danrui Ruan; Mengjuan Zhang; Shihua Wang (Environmental Microbiology, 2022)
Summary Myst family is highly conserved histone acetyltransferases in eukaryotic cells and is known to play crucial roles in various cellular processes; however, acetylation catalysed by acetyltransferases is unclear in filamentous fungi. Here, we identified two classical nonessential Myst enzymes and analysed their functions in Aspergillus flavus , which generates aflatoxin B1, one of the most carcinogenic secondary metabolites. MystA and MystB located in nuclei and cytoplasm, and mystA could acetylate H4K16ac, while mystB acetylates H3K14ac, H3K18ac and H3K23ac. Deletion mystA resulted in decreased conidiation, increased sclerotia formation and aflatoxin production. Deletion of mystB leads to significant defects in conidiation, sclerotia formation and aflatoxin production. Additionally, double‐knockout mutant (Δ mystA / mystB ) display a stronger and similar defect to Δ mystB mutant, indicating that mystB plays a major role in regulating development and aflatoxin production. Both mystA and mystB play important role in crop colonization. Moreover, catalytic domain MOZ and the catalytic site E199/E243 were important for the acetyltransferase function of Myst. Notably, chromatin immunoprecipitation results indicated that mystB participated in oxidative detoxification by regulating the acetylation level of H3K14, and further regulated nsdD to affect sclerotia formation and aflatoxin production. This study provides new evidences to discover the biological functions of histone acetyltransferase in A . flavus .

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

CRISPR/Cas9-mediated somatic and germline gene correction to restore hemostasis in hemophilia B mice - Cong Huai; Chenqiang Jia; Ruilin Sun; Peipei Xu; Taishan Min; Qihan Wang; Chengde Zheng; Hongyan Chen; Daru Lu (Human Genetics, 2017)

Ecological Network Analysis of Embodied Energy Exchanges Among the Seven Regions of China - Yan Zhang; Hongmei Zheng; Bin Chen; Xiangyi Yu; Klaus Hubacek; Ruilin Wu; Xiaoxi Sun (Journal of Industrial Ecology, 2016)
Summary Regional economic development in China has resulted in an unbalanced distribution of resources and frequent exchanges of resources and products among regions. Therefore, it is necessary to understand these regional differences to support national planning to improve sustainability. In this research, we used energy data and a multiregional input‐output table for China in 2002 to analyze the domestic trade among the 30 provinces and seven regions of China. We also quantified the embodied energy flows and their patterns by means of ecological network analysis and looked at different types of relationships between the regions, such as mutualistic or competing relationships. The results show that the flows connected with the Northern and Eastern regions ranked first, and those connected with the Southwestern and Northwestern regions were the smallest. Based on the flows among provinces and regions, we determined the relationships among them. Results show that more than 95% of the total relationships among the regions were exploitation, with only one competition relationship. The Eastern region received the largest input and the highest benefits from their energy exchanges with other regions. Our study of the regional flows and relationships among the regions and provinces provides useful information on the flows and consumption of embodied energy in China, thereby providing insights into the sustainability of these flows and how to promote sustainable development through regional cooperation.

Seroprevalence of Brucella infection in yaks (Bos grunniens) on the Qinghai–Tibet plateau of China - Lang Xulong; Qu Hailong; Bu Zhaoyang; Yang Yanling; Sun Chunhui; Li Xiaoyan; Wang Jinglong; Cai Jinshan; Ma Ruilin; Fu Yijuan; Wang Xinglong (Tropical Animal Health and Production, 2011)